Reasons for Permanent Tooth Extractions in Japan - Aida, Jun (J Epidemiol, 2006)
BACKGROUND: There has been no nationwide study in Japan on reasons for extraction of permanent teeth. This survey was aimed to determine the reasons for extraction of permanent teeth in Japan. METHODS: Five thousand, one hudred and thirty-one dentists were selected by systematic selection from the 2004 membership directory of the Japan Dental Association. The dentists selected were asked to record the reason for each extraction of permanent teeth during a period of one week from February 1 through 7, 2005. Reasons for tooth extraction were assigned to five groups: caries, fracture of teeth weakened by caries or endodontics, periodontal diseases, orthodontics, and other reasons. RESULTS: A total of 2,001 dentists (response rate of 39.1%) returned the questionnaires, and information on 9,115 extracted teeth from 7,499 patients was obtained. The results showed that caries and its sequela (totally 43.3%, 32.7% and 10.6%, respectively) and periodontal disease (41.8%) were the main reasons for teeth extraction. Extraction due to caries or fracture was commonly observed in all age groups over 15 years of age, whereas periodontal disease was predominant in the groups over 45 years of age. CONCLUSIONS: Most of the permanent teeth were extracted due to caries and its sequela and periodontal disease. Prevention and care for dental caries for all age groups and periodontal disease for over middle age groups are required.